An approach to the in vitro study of the UTP/UDPglucose/UDP moiety-conserved cycle - Fassy, F; Hervagault, J F (Biochimica et biophysica acta, 1994)
The kinetic behavior of a moiety-conserved ternary cycle is tested experimentally. This system contains the enzymes UDPglucose pyrophosphorylase, glycogen synthase and nucleoside diphosphokinase, converting respectively UTP into UDPglucose, then into UDP and back to UTP in a cyclic manner. The UDPGlc P2ase and NDPK steps are made irreversible by addition of inorganic pyrophosphatase and phosphocreatine kinase, respectively. In order to predict both the evolution and the steady-state values of the various substrates, a model is derived, which takes into account the actual enzyme rate expressions and parameter values, as determined under our experimental conditions. In that model, the UTP, UDPglucose and UDP are taken as the variables, whereas the total concentration of the substrate pool and the four enzyme maximal activities are chosen as the control parameters. Depending upon the various parameter values, monostability, reversible bistability and irreversible transitions may theoretically occur. However, it turns out that some of these values for which multistability might occur, are not accessible experimentally. Under conditions of monostability, the evolutions of the three substrates as experimentally measured are shown to be in good qualitative and quantitative agreement with the model predictions. The relaxation times between two consecutive steady states when a parameter is varied, are shown to be long-lasting processes (several hours). That such an experimental ternary substrate cycle actually exhibits a low sensitivity to any perturbation, addresses the issue to knowing if the same property is likely to occur in vivo, or, in other words, do large moiety-conserved cycles act as metabolic buffers?